Collective pursuit for equity in cancer care: The National Navigation Roundtable. (14th June 2022) - Dwyer, Andrea J.; Wender, Richard C.; Weltzien, Elsa S.; Dean, Monica S.; Sharpe, Katherine; Fleisher, Linda; Burhansstipanov, Linda; Johnson, Wenora; Martinez, Laura; Wiatrek, Dawn E.; Calhoun, Elizabeth; Battaglia, Tracy A.; et al.
Abstract : BACKGROUND: The evidence continues to build in support of implementing patient navigation to reduce barriers and increase access to care. However, health disparities remain in cancer outcomes. The goal of the National Navigation Roundtable (NNRT) is to serve as a convener to help support the field of navigation to address equity. METHODS: To examine the progress and opportunities for navigation, the NNRT submitted a collection of articles based on the results from 2 dedicated surveys and contributions from member organizations. The intent was to help inform what we know about patient navigation since the last dedicated examination in this journal 10 years ago. RESULTS: The online survey of >700 people described navigators and examined sustainability and policy issues and the longevity, specific role and function, and impact of clinical and nonclinical navigators in addition to the role of training and supervision. In addition, a full examination of coronavirus disease 2019 and contributions from member organizations helped further define progress and future opportunities to meet the needs of patients through patient navigation. CONCLUSIONS: To achieve equity in cancer care will demand the sustained action of virtually every component of the cancer care system. It is the hope and intent of the NNRT that the information presented in this supplement will be a catalyst for action in this collective action approach. Abstract : To achieve equity in cancer care will demand the sustained action of virtually every component of the cancer care system. It is the hope and intent of the National Navigation Roundtable that the information presented in this supplement will be a catalyst for action in this collective action approach.